A teoria da ação e o mal-estar na civilização : nada há para a felicidade além do princípio do prazer? - Vedana, Simone Teresinha (My University, 2024)
The research aims to analyze ethical-philosophical aspects regarding training and mental health based on the Aristotelian philosophical approach and psychoanalytic theory. In view of these two approaches, the possibility of theoretical compatibility between Aristotle's philosophy and the revolutionary psychoanalytic theory regarding the constitution of the psychic character, which deals with sanity and psychopathology, is investigated. Is it possible that the explanations about moral character in Aristotle and Freud converge into compatible theories that in some aspects complement each other on the structure and psychic development, both healthy and pathological? Average rational control of pleasures, habit formation and education of sensations and emotions can be directly related to mental health. Through the dialectical analysis of Aristotelian and Freudian theory, some common foundations are sought for understanding the mental condition and human character. Aristotelian theory establishes some concepts about ethical and dianoetic virtues, attributing to them the moderating function of appetites, affections and emotions as the first moral precepts for the individual to have a virtuous character. The condition established for these first capabilities consists of an ability of the individual-collective organism to take practical actions and through rational means that aim at the common good. Temperance is the virtuous moral disposition that makes the individual able to design the course with balance and harmony between passion and reason, aiming for the best ends of their desires. A virtuous life is also a primordial condition for community life, as the individual who develops the moral capacity to direct their desires and affections towards the best end and the common good may also need an ethical disposition called phronesis. The opposite of these dispositions are the lack of control and bad, sensitive and perceptive designs that confer pathological traits of vicious behavior, found in the intemperate and incontinent character. Vices tend to be obstacles to other dianoetic dispositions, practical and scientific wisdom. The compulsive character, for example, tends to repeat deliberate bad actions. Aristotelian ethics advocates ethical virtues and dianoethics as conditions for the acquisition of the common good and the highest, a happy life. In contemporary literature it is possible to infer the condition of how this disposition to addiction, already mentioned in ancient Greek philosophy, can be constituted. Freudian psychoanalysis highlights, through its analytical observation of behavior and speech, some forms that reflect the condition of emotional and affective suffering and compulsive actions. What is attributed to the condition of suffering is what in psychoanalysis was called a symptom and the passive and active agent is a condition of what the psychoanalyst called neurosis. The origins of these conditions of suffering are symptomatic evidence that acts through the repetition of sensitive perceptions and affective relationships that require to be elaborated emotionally and consciously. [resumo fornecido pelo autor]
A pesquisa visa analisar aspectos ético-filosóficos a respeito da formação e da saúde psíquica com base na abordagem filosófica aristotélica e da teoria psicanalítica. Diante dessas duas abordagens investiga-se a possibilidade de compatibilidade teórica entre a filosofia de Aristóteles e a revolucionária teoria psicanalítica a respeito da constituição do caráter psíquico que versa entre a sanidade e a psicopatologia. É possível que as explicações sobre o caráter moral em Aristóteles e em Freud convirjam em teorias compatíveis e que em alguns aspectos se complementam sobre a estrutura e o desenvolvimento psíquico tanto saudável quanto o patológico? A mediania no controle racional dos prazeres, a formação do hábito e a educação das sensações e emoções podem estar diretamente relacionadas à saúde mental. Através da análise dialética da teoria aristotélica e freudiana, alguns fundamentos comuns são buscados para a compreensão da condição mental e do caráter humano. A teoria aristotélica estabelece alguns conceitos sobre as virtudes éticas e dianoética, atribuindo sobre elas a função moderadora dos apetites, afetos e das emoções como primeiros preceitos morais para o indivíduo dispor de um caráter virtuoso. A condição estabelecida para essas primeiras capacidades consiste em uma habilidade do organismo indivíduo-coletivo para ações práticas e por meios racionais que visam o bem comum. A temperança é a disposição moral virtuosa que torna o indivíduo apto a designar o curso com equilíbrio e harmonia entre paixão e razão, visando os melhores fins aos seus desejos. A vida virtuosa é também uma condição primordial para a vida em comunidade, pois o indivíduo que desenvolve a capacidade moral em direcionar os seus desejos e afetos para o melhor fim e para o bem comum precisa também de uma disposição ética denominada por phronesis. O contrário dessas disposições são os descontroles e maus desígnios sensíveis e perceptivos que conferem traços patológico do comportamento vicioso, encontrado no caráter intemperante e incontinente. Os vícios tendem a ser obstáculos para as demais disposições dianóeticas, a sabedoria prática e a científica. O caráter compulsivo, por exemplo, tende a repetição das ações más deliberadas. A ética aristotélica preconiza as virtudes éticas e dianoética como condições para a aquisição do bem comum e o mais elevado, a vida feliz. Na literatura contemporânea é possível inferir sobre a condição de como pode ser constituído essa disposição ao vício, já mencionado na antiga filosofia grega. A psicanálise freudiana evidencia, através de sua observação analítica do comportamento e do discurso, algumas formas que traduzem a condição de sofrimento emocional e afetivo e as ações compulsivas. O que é atribuído à condição de sofrimento, é o que na psicanálise foi denominado como sintoma e o agente passivo e ativo é uma condição do que o psicanalista denominou como neurose. As origens dessas condições de sofrimento são evidências sintomáticas que atuam por repetição das percepções sensíveis e as relações afetivas que requerem ser elaboradas emocionalmente e conscientemente. [resumo fornecido pelo autor]
Keywords: Ética; Caráter; Filosofia; Psicanálise; Desejo; Ethics; Character; Philosophy; Psychoanalysis; Desire